Semi-nonoscillation intervals and sign-constancy of Green’s functions of two-point impulsive boundary-value problems - Domoshnitsky, A.; Mizgireva, Iu.; Raichik, V.; Домошнитский, Александр; Mizgireva, Iuliia; Domoshnitsky, A.; Mizgireva, Iu.; Raichik, V. (Institute of Mathematics, NAS of Ukraine, 2021)
UDC 517.9